Investigating the roles of microRNAs associated with cancer stem cells, drug resistance, metastasis and recurrence in hepatocellular carcinoma: a systematic review, network analysis and experimental verification - Jiang, Yuanyuan; Zhu, Xiaoning; Peng, Qinghua; Dastjerdi, Paniz Zarghami; Peng, Mengyun; Zheng, Ding; Wang, Xiaodong; Cheah, Yoke Kqueen; Wang, Jing (Spandidos Publications, 2025)
Cancer stem cells (CSCs) are responsible for drug therapy resistance, recurrence and metastasis in hepatocellular carcinoma (HCC). Certain microRNAs (miRNAs/miRs) are involved in various pathological cancer pathways via their binding interactions with target mRNAs. The objectives of the present study were to explore the potential microRNAs associated with HCC‑CSCs, and to investigate their roles in recurrence, metastasis and drug resistance. Initially, a regis‑ tered systematic review (CRD42024508526; International Prospective Register of Systematic Reviews) identified a group of miRNAs associated with HCC prognosis, and the Coremine Medical data mining tool identified another group of potential miRNAs associated with HCC‑CSCs, recurrence, metastasis and drug resistance. Secondly, potential miRNAs that were associated with HCC prognosis, CSCs, recurrence, metastasis and drug resistance were detected by comparing the two groups of miRNAs. Subsequently, the expression levels of a potential miRNA in HCC tissues and its prognostic predictive power were evaluated using the Encyclopedia of RNA Interactomes and Kaplan‑Meier plotter online tools. In addition, the expres‑ sion levels of the target miRNA in Huh7‑CSCs and Huh7 cells were measured using reverse transcription‑quantitative PCR (RT‑qPCR). Finally, the potential biological processes of the miRNA target genes were examined through bioinformatics analysis using the Enrichr database. Briefly, hsa‑miR‑17‑5p was predicted to be associated with stemness, metastasis, recurrence and drug resistance in HCC. Bioinformatics analysis demonstrated that miR‑17‑5p expression was higher in HCC tissues compared with that in para‑tumor tissues and that patients with low miR‑17‑5p expression demonstrated higher overall survival rates (months). The RT‑qPCR results indicated that miR‑17‑5p expression in Huh7‑CSCs was significantly higher compared with that in Huh7 cells. Further bioinformatics analysis suggested that miR‑17‑5p maintains stemness by targeting hypoxia‑inducible factor‑1α (HIF1A) and Myc. Additionally, the target genes of miR‑17‑5p were revealed to be involved in cell fate and metabolic reprogram‑ ming pathways. In conclusion, miR‑17‑5p may be a potential miRNA associated with CSCs, metastasis, recurrence and drug resistance in HCC via cell fate and metabolic reprogram‑ ming pathways. miR‑17‑5p exhibited higher expression in HCC‑CSCs compared with that in HCC cell lines, and may target HIF1A and Myc to maintain HCC‑CSCs stemness.